New Family Members of FG Repeat Proteins and Their Unexplored Roles During Phase Separation - Shinkai, Yoichi; Kuramochi, Masahiro; Miyafusa, Takamitsu (Frontiers in Cell and Developmental Biology, 2021)
The condensation and compartmentalization of biomacromolecules in the cell are driven by the process of phase separation. The main effectors of phase separation are intrinsically disordered proteins, which include proteins with a phenylalanine-glycine (FG) repeat domain. Our understanding of the biological function of FG repeat proteins during phase separation has been mainly derived from recent research on a member of the nuclear pore complex proteins, nucleoporins containing FG repeat domain (FG-NUPs). FG-NUPs form meshwork structures by inter- and intra-molecular FG domain interactions, which confine the nucleo-cytoplasmic exchange. Whereas FG-NUPs localize in the nuclear membrane, other FG repeat proteins reside in the cytoplasm and the nucleoplasm, and the biological function of the FG repeat domain of these proteins is not well described. In the present review, we list the FG repeat proteins that are known to phase separate in the cell, and review their biological functions. We extract the unraveled features of FG repeat proteins as an activator of barrier formation and homotypic cell-cell interactions. Understanding the regulatory mechanisms of FG repeat proteins will provide a potential delivery tool for therapeutic reagents.